Antioxidant and antimicrobial activities of European hackberry (Celtis australis L.) seeds - Alonso-Esteban, José Ignacio (2019)
The European hackberry (Celtis australis L.) is a deciduous tree of the Cannabaceae family frequently found in southern Europe and western Asia. Its fruit is an edible, dark-purple berry-like drupe with a large seed that corresponds to about 38% of the fruit dry weight [ l ]. Fruit preparations are used in traditional medicine as a remedy for colic, peptic ulcers, dysentery, diarrhea, amenorrhea, and heavy menstrual bleeding [1-3]. However, as far as we know, the antioxidant and antimicrobial properties of C. australis seeds have never been explored before, being this the purpose ofthis study. The C. australis seed extract was obtained by a solid-liquid extraction of the powdered sample with methanol water (80:20, v/v) [4]. Then, the antioxidant activity was measured in vitro via DPPH' scavenging activity, reducing power, p-carotene bleaching inhibition capacity, and thiobarbituric acid reactive substances (TBARS) formation inhibition capacity in brain cell homogenates [4]. The antimicrobial activity was screened against twelve microorganisms, including Gram-positive and Gram-negative bactéria and fungi, by the microdilution method [5]. The seed extract was effective in inhibiting the formation of TBARS as byproducts Of lipid peroxidation, which was concluded from the low EC^ value. The extract also had an interesting reducing power and capacity to protect p-carotene from the free radicais generated from linoleic acid. Regarding its antimicrobial activity, the best results were against B. cereus, with MIC and MBC lower than ampicillin, A. ochraceus, with MIC and MFC lower than ketoconazole, and P. funiculosum, with MIC lower than ketoconazole and bifonazole and MFC lower than ketoconazole. These results highlighted the potential of C. australis seeds as an interesting fruit byproduct to be used in the development of bio-based antimicrobials.